ANALISIS RASIO KEUANGAN PADA RUMAH MAKAN DARISA DI KOTA PALU - ARDIANSYAH, ARDIANSYAH (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
In order to support competition in company, needed system of record in manage company financial to understand how far level of company performance in control its financial. From the financial report, here, we can see the level of financial ratio used analysis of ratio. The issue used is How financial ratio of Darisa Restaurant in Palu which is measured Liquidity ratio, solvability ratio, activity ratio and rentability ratio.Ratio of Liquidity (Quick Ratio) in last 5 years is fluctuating. In 2012 until 2016, shown that Darisa Restaurant still afford to pay his current liabilities. On this situation, Darisa Restaurant financial, seen from Quick Ratio is liquid. In Ratio of Solvability from Darisa Restaurant if measured from total of debt divided total of assets, draws company condition in 2012, 2013, and 2014 was bad. Meanwhile, in 2016 and 2015 company was good. If the ratio is high,it means funding with debt is increased. So, it's harder for company to accept new debt because worried that company unaffordable to cover the debt with its assets.